Soluble Ectodomain of Neuroligin 1 Decreases Synaptic Activity by Activating Metabotropic Glutamate Receptor 2 - Gjørlund, Michelle D.; Carlsen, Eva M. M.; Kønig, Andreas B.; Dmytrieva, Oksana; Petersen, Anders V.; Jacobsen, Jacob; Berezin, Vladimir; Perrier, Jean-François; Owczarek, Sylwia (Frontiers in Molecular Neuroscience, 2017)
Synaptic cell adhesion molecules represent important targets for neuronal activity-dependent proteolysis. Postsynaptic neuroligins (NLs) form trans-synaptic complexes with presynaptic neurexins (NXs). Both NXs and NLs are cleaved from the cell surface by metalloproteases in an activity-dependent manner, releasing a soluble extracellular fragment and membrane-tethered C-terminal fragment. The cleavage of NL1 depresses synaptic transmission, but the mechanism by which this occurs is unknown. Metabotropic glutamate receptor 2 (mGluR2) are located primarily at the periphery of presynaptic terminals, where they inhibit the formation of cyclic adenosine monophosphate (cAMP) and consequently suppress the release of glutamate and decrease synaptic transmission. In the present study, we found that the soluble ectodomain of NL1 binds to and activates mGluR2 in both neurons and heterologous cells, resulting in a decrease in cAMP formation. In a slice preparation from the hippocampus of mice, NL1 inhibited the release of glutamate from mossy fibers that project to CA3 pyramidal neurons. The presynaptic effect of NL1 was abolished in the presence of a selective antagonist for mGluR2. Thus, our data suggest that the soluble extracellular domain of NL1 functionally interacts with mGluR2 and thereby decreases synaptic strength.